Surgical management of inflammatory eye disease - Becker, Matthias D. (Springer, 2017)
Ocular inflammation presents a broad spectrum of clinical manifestations. Inflammatory activity can often be managed by drug therapy. However, inadequate medical therapy may permit the development of various complications in the eye that cannot be sufficiently treated pharmacologically. Whereas drug management demands an interdisciplinary approach with well-trained specialists, surgical treatment of ocular complications due to inflammation requires an experienced surgeon.